Application of the transgenic pig model in biomedical research: A review - Wei, Jialin; Zhang, Wen; Li, Jie; Jin, Ye; Qiu, Zhidong (Frontiers in Cell and Developmental Biology, 2022)
Large animal model gradually become an essential part of preclinical researches, relating to exploring disease pathological mechanism, genic function, pharmacy and other subjects. Due to different body functions and systems between mice and human, the need of find an animal 19model with high similarity comparing with human. Pig is an optimal choice for replacement. Therefore, enhancing production of pig used for models is an important part in large animal model as well. Transgenic pig shows superiority in pig model creation because of the progress in genetic engineering. Successful cases of transgenic pig model occur in the clinical field of metabolic diseases, neurodegenerative diseases, and genetic diseases. In addition, the choice of pig breed influences the effort and efficiency of reproducing, and mini pig has a relative longer period of breeding. This review briefly outlines the method used to create transgenic pigs, species of producing transgenic pigs and provides an overview of their applications on different diseases and how the aspect needs to be considered in the near future researches.